2001
DOI: 10.1034/j.1600-0722.2001.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic characterization of serologically untypable Streptococcus mutans strains isolated from patients with bacteremia

Abstract: Four out of 522 streptococcal isolates from the peripheral blood of patients with bacteremia exhibited typical properties of Streptococcus mutans in terms of sucrose-dependent adhesion, expression of glucosyltransferases, fermentation profiles of sugars, the presence of surface protein antigen, and DNA-DNA hybridization. Two strains were determined as serotype f and e by immunodiffusion, whereas the other two isolates did not react with the specific antiserum to S. mutans serotype c. e. or f of the eight diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…The inability of certain strains to utilize b-glucosides is also associated with deletions in the bgl or cel genes (Old et al, 2006). Other researchers have reported that genes required for formation of serotypespecific polysaccharide are absent from untypable isolates (Fujiwara et al, 2001). There is also evidence for the existence of genes in some strains of S. mutans that are not found in UA159.…”
Section: Introductionmentioning
confidence: 74%
“…The inability of certain strains to utilize b-glucosides is also associated with deletions in the bgl or cel genes (Old et al, 2006). Other researchers have reported that genes required for formation of serotypespecific polysaccharide are absent from untypable isolates (Fujiwara et al, 2001). There is also evidence for the existence of genes in some strains of S. mutans that are not found in UA159.…”
Section: Introductionmentioning
confidence: 74%
“…The amplified fragments were visualized in 0.7 % agarose gel in the presence of 1 mg ethidium bromide ml 21 . For all detections, strains TW871 and MT8148 (Fujiwara et al, 2001;Ooshima et al, 1983) were used as positive and negative controls, respectively. Analysis of clonal relationship using MLST.…”
Section: Methodsmentioning
confidence: 99%
“…The amplified fragments were visualized in 0.7 % agarose gel in the presence of 1 mg ethidium bromide ml 21 . For all detections, strains TW871 and MT8148 (Fujiwara et al, 2001;Ooshima et al, 1983) were used as positive and negative controls, respectively.Analysis of clonal relationship using MLST. One S. mutans strain possessing the cnm gene from each subject was randomly selected and analysed by the MLST scheme, as described previously (Nakano et al, 2007).…”
mentioning
confidence: 99%
“…The colony morphology of these strains on agar plates was apparently different from that of typical S. mutans strains, whereas it was similar to strains generated by inactivation of the genes encoding GTFs (Ooshima et al, 2001). As the occurrence of S. mutans without GTF expression is extremely rare in the oral cavity, we performed molecular characterization of the GTFs in the V1 strain isolated from the infected heart valve of this patient and speculate on its origin based on the results of strain-specific characterization.…”
Section: Introductionmentioning
confidence: 92%
“…The bacterium synthesizes adhesive glucan from sucrose by the action of three types of glucosyltransferase (GTF: GTFB, GTFC and GTFD), each of which, at an optimum ratio, has been shown to be important for sucrose-dependent adherence (Ooshima et al, 2001). GTFs are known to be important virulence factors of S. mutans for dental caries, as inactivation of the genes encoding each GTF results in a drastic reduction in caries-inducing activity in animal experiments (Yamashita et al, 1993).…”
Section: Introductionmentioning
confidence: 99%